CROSS-LINGUISTIC INFLUENCE IN SECOND LANGUAGE PHONOLOGY - Khudoyorov Omonjon Tursunovich (Web of Journals Publishing, 2025)
This article explores the issue of phonological interference that arises in the process of second language acquisition. Phonological interference refers to the influence of a speaker’s native language sound system on the pronunciation of a target language. The paper highlights the major causes of such interference, including the absence of equivalent phonemes in the learner’s first language, differences in articulation habits, and phoneme positioning within words. Examples from various language pairs are provided to illustrate how native phonology affects second language pronunciation. Furthermore, the article presents practical strategies for minimizing phonological interference, such as phonetic training, contrastive phoneme analysis, and the use of authentic audio materials. Overall, the study emphasizes the importance of developing phonological awareness in order to achieve accurate and intelligible pronunciation in a foreign language.
Keywords: Cross-linguistic influence, second language acquisition, phonological transfer, L1 interference, phonemic contrast, phonological interference, pronunciation errors, phonemic differences, interlanguage phonology.